1993
DOI: 10.3109/00016489309135812
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cochlear Hearing Loss Results in Developmental Abnormalities of the Central Auditory Pathways

Abstract: We have used animal models of long term neonatal cochlear hearing loss to study developmental plasticity of the central auditory pathways. Newborn chinchilla pups and feline kittens were treated with the ototoxic drug amikacin, so as to induce basal lesions in the cochlea. At maturity these animals were used in single unit electrophysiological mapping studies, in which the cochleotopic organization of primary auditory cortex (of the cat) and the inferior colliculus of the midbrain (in the chinchilla) were mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…It is well established that the auditory cortex -like the visual, the somatosensory and the motor cortex -exhibits a remarkable plasticity. Microelectrode studies in different laboratory animals have shown that several months after a partial cochlear lesion the deprived area of the contralateral primary auditory cortex (A1) has undergone an extensive reorganization [Robertson and Irvine, 1989;Harrison et al, 1991Harrison et al, , 1993bRajan et al, 1993;Schwaber et al, 1993;Rajan and Irvine, 1998]. In the case of unilateral cochlear lesions the contralateral A1 was altered so that the A1 region in which frequencies with lesion-induced elevations in cochlear neural sensitivity would have been represented was occupied by an enlarged representation of lesion-edge frequencies (i.e., frequencies adjacent to those with elevated cochlear neural sensitivity).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the auditory cortex -like the visual, the somatosensory and the motor cortex -exhibits a remarkable plasticity. Microelectrode studies in different laboratory animals have shown that several months after a partial cochlear lesion the deprived area of the contralateral primary auditory cortex (A1) has undergone an extensive reorganization [Robertson and Irvine, 1989;Harrison et al, 1991Harrison et al, , 1993bRajan et al, 1993;Schwaber et al, 1993;Rajan and Irvine, 1998]. In the case of unilateral cochlear lesions the contralateral A1 was altered so that the A1 region in which frequencies with lesion-induced elevations in cochlear neural sensitivity would have been represented was occupied by an enlarged representation of lesion-edge frequencies (i.e., frequencies adjacent to those with elevated cochlear neural sensitivity).…”
Section: Discussionmentioning
confidence: 99%
“…This functional development is substantially influenced by the structure of environmental acoustic inputs in early life, especially within a critical-period time window when the system is most susceptible to alteration by environmental auditory inputs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Introduction of synchronous inputs into the auditory pathway achieved by exposing rat pups to pulsed noise during this time window, for example, results in a disrupted tonotopicity and broader-than-normal frequency tuning curves in the primary auditory cortex (A1).…”
mentioning
confidence: 99%
“…A uditory experience plays an important role in the development of the primary auditory cortex (A1) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Exposure of kittens or rat pups to a modulated tonal stimuli during an early postnatal period resulted in an expansion of the representation of the exposed sound frequency in A1 (2,7).…”
mentioning
confidence: 99%